„Едната воплотена природа на Бога Словото“ - Од Аполинариј Лаодикиски до свети Кирил Александриски - Nedeski, Viktor (Православен богословски факултет „Св. Климент Охридски“ Скопје, 2020)
Immediately after the First Ecumenical Council (325 A. D.), the question of the completeness of the human nature of Jesus Christ was raised by the Arian Anomians, who claimed that the Word of God received only a “soulless body,” that is, that it took the place of the soul in man. Apollinarius of Laodicea tried to answer the question of the completeness of the human nature of the Lord Jesus Christ. The phrase of Apollinarius is characteristic: “one incarnate nature of the Word” which is stated in his confession to Jovian. This phrase is widely used by St. Cyril of Alexandria, who, according to most scholars, considered it a phrase of St. Athanasius the Great. St. Cyril gives an Orthodox interpretation to this controversial phrase, freeing it from any apollinaristic teaching. The Alexandrian father meant that Christ was one person with two perfect natures, divine and human, rejecting all forms of monophysitism. Thus, only as a perfect God and man, Jesus Christ can save man from death and sin and reconcile him with God - something that the first Adam failed to do.